(untitled) - T S Blyth (Cambridge, 1984)
The book provides a selection of problems with complete solutions and test papers designed to be used with or instead of standard textbooks on algebra. It offers a understanding of the fundamental concepts involved, and practice in the formulation, and so solution, of other algebraic problems. This book begin with some notes on notation and prerequisites
Keywords: algebra - problems, exercises, etc